Valorising Nutrient-Rich Digestate as a Waste-Based Media for Microalgal Cultivation: Bench-Scale Filtration Characterisation and Scale-Up for a Commercial Recovery Process - Yilu Xu; James Russell; Gahtan S. M. Algahtani; Darren L. Oatley-Radcliffe (Energies, 2022)
Cultivating microalgae requires a nitrogen and phosphorous feed source. Anaerobic digestion waste (digestate) provides a cheap sustainable feedstock for these materials. Previous studies have successfully demonstrated the feasibility of nutrient recovery and subsequent algae growth. There is now a need to fully characterise digestate filtration to improve our understanding of this process prior to its commercialisation. In this work, digestate filtration is characterised at bench scale using frontal (dead-end) filtration and a 100 kDa MWCO ultrafiltration membrane. Our experiments demonstrated rapid cake formation causing significant flux decline. The steady-state permeate flux for digestate was 2.4 to 4.8 L m−2 h−1, a reduction of ~90% compared to clean water flux. The specific cake resistance was ~1015 m kg−1 and the compressibility index 1.07. A series of four filtration and cleaning cycles showed 90% flux recovery following a clean water wash. Digestate filtration was then evaluated at a commercial scale using crossflow and the KOCH ABCOR® tubular membrane (100 kDa MWCO). The results were similar to those at the bench scale, i.e., rapid initial fouling leading to a period of steady-state flux (approximately 7 L m−2 h−1). The commercial membrane was flushed with water and diluted bleach after each use, and a digestate permeate flux decline of only 4.8% over a 12-month active use period was observed. The present research provides bench scale characterisation and demonstrates the commercial scale operation of anaerobic digestate filtration using ultrafiltration. The overall filtration performance was excellent, and the process can now be scaled to any operational capacity.